Socio-Economic Realities at Work: a Study on Female Workers in the SME’s Located in Malaysia - Karubi, Nwanesi Peter (Information Management and Business Review, 2012)
This paper attempted to critically analyse the social/cultural issues faced by women in SME’s located in Penang Island in the heart of Malaysia. Further, it aimed to evaluate the motives and the impact of changing jobs among the Female Factory Workers (FFW) at the SME factories located in Penang Island. SME’s are mainly based on 5 to 250 employees. However, the technical definition varied from country to country in the Asia-Pacific region but was usually based on employment, assets, or a combination of the two. Some countries had different definitions for SME’s in the manufacturing and services sector and may exempt firms from specialized industries or firms that had shareholdings by parent companies. The trends in many SME’s’ factories were to employ a large number of young girls from rural areas or other neighbouring states. The findings of the study depicted that the young women were often underpaid, housed in over-crowed hostels and some often-experienced sexual harassment and salaries withheld.